Gene Editing of Hematopoietic Stem Cells: Hopes and Hurdles Toward Clinical Translation - Ferrari, Samuele; Vavassori, Valentina; Canarutto, Daniele; Jacob, Aurelien; Castiello, Maria Carmina; Javed, Attya Omer; Genovese, Pietro (Frontiers in Genome Editing, 2021)
In the field of hematology, gene therapies based on integrating vectors have reached outstanding results for a number of human diseases. With the advent of novel programmable nucleases, such as CRISPR/Cas9, it has been possible to expand the applications of gene therapy beyond semi-random gene addition to site-specific modification of the genome, holding the promise for safer genetic manipulation. Here we review the state of the art of ex vivo gene editing with programmable nucleases in human hematopoietic stem and progenitor cells (HSPCs). We highlight the potential advantages and the current challenges towards safe and effective clinical translation of gene editing for the treatment of hematological diseases.